EFFECT OF PHYSICO-CHEMICAL PARAMETERS ON THE ABUNDANCE AND DIVERSITY OF TERMITES AND OTHER ARTHROPODS IN TERMITE MOUNDS IN UYO, AKWA IBOM STATE, NIGERIA - Akpan, Akaninyene U.; Ojianwuna, C. C.; Ubulom, P. M. E.; Yaro, C. A.; Oboho, D. E. (FUDMA JOURNAL OF SCIENCES, 2020)
Termites are generally regarded as pests, although they have some beneficial roles to play in the ecosystem, particularly in the soil. This study was conducted between January 2018 and April 2018, to determine the effect of physico-chemical parametrs on abundance and diversity of termites and other arthropods in termite mounds in Uinversity of Uyo Community. Soil samples were randomly collected from six termite mounds from two sites for physiochemical parameters analysis and these were temperature, pH, moisture content, nitrogen, phosphorus, magnesium, copper, sodium, potassium, manganese and iron.. The termites and other arthropods were preserved in 70% ethanol. Temperature and moisture content, copper, sodium and iron were significant. The results revealed that the physicochemical parameters affected the termite species abundance as station 1 (539) had relatively more of the termite species than station 2 (551), and also affected the diversity of the termites as station 1 (0.89) had relatively more diversity of the termites than station 2 (0.66). Also from the results, station 1 (2.06) had relatively more diversity of the other arthropod species identified in the study area than station 2 (1.59). Macrotermes bellicosus and Odontermes badius termite species were identified. Musca domestica, Anopheles gambiae, Lasius sp, Archispirostreptus sp, Camponotus sp, Missulena sp, Chorthippus sp, Acheta sp and Blatta orientalis were the other arthropods collected and identified. Macrotermes bellicosus (59.93 %; 63.52 %) was the most abundance and dorminant of the termite species identified in the study areas. Lasius sp (45; 25.93 %)